Fiscal Coverage in the Countries of the Middle East and Central Asia : Current Situation and a Way Forward - Zakharova, Daria (IMF Working Papers; Working Paper ;, 2008)
This paper reviews some broad principles of fiscal coverage, building on cross-country experience. It discusses the level of coverage that would be appropriate to conduct good quality fiscal analysis, while striking the right balance between the costs and the benefits of expanding the coverage. In this context, the paper examines the current status of statistical fiscal coverage in the countries of the Middle East and Central Asia (MECA), and proposes operational approaches to improving it.